HIGH SEQUENCE DIVERSITY IN THE RNA SYNTHESIZED AT THE LAMPBRUSH STAGE OF OÖGENESIS - Davidson, Eric H. (1969)
Many diverse RNA's are synthesized in the lampbrush stage oöcyte of Xenopus, as shown by the presence of different nucleotide sequences in the RNA population. This fact has been established by hybridizing lampbrush stage oöcyte RNA with an isolated nonrepetitive fraction of Xenopus DNA.